Predictive factors of alcohol and tobacco use in adolescents - Alicia Alvarez-Aguirre; María Magdalena Alonso-Castillo; Ana Carolina Guidorizzi Zanetti (Universidade de São Paulo, 2014)
OBJECTIVES: to analyze the effect of self-esteem, assertiveness, self-efficacy and resiliency on alcohol and tobacco consumption in adolescents.METHOD: a descriptive and correlational study was undertaken with 575 adolescents in 2010. The Self-Esteem Scale, the Situational Confidence Scale, the Assertiveness Questionnaire and the Resiliency Scale were used.RESULTS: the adjustment of the logistic regression model, considering age, sex, self-esteem, assertiveness, self-efficacy and resiliency, demonstrates significance in the consumption of alcohol and tobacco. Age, resiliency and assertiveness predict alcohol consumption in the lifetime and assertiveness predicts alcohol consumption in the last year. Similarly, age and sex predict tobacco consumption in the lifetime and age in the last year.CONCLUSION: this study can offer important information to plan nursing interventions involving adolescent alcohol and tobacco users.